PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.D SMP ISLAM TERPADU BANGKINANG - Putri Arum Kasuma; Syofni '; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve learning process and to increase the mathematic learning evaluation by implying cooperative learning of Talking Stick. The subjects of this research are student in grade VIIID of SMP Islam Terpadu Bangkinang at the second semester of academic year 2015/2016. Total number of participant are 23 whose academic achievement are heterogen. This research have 2 cycles, each cycle have four stages: planning, implementation, observation, and reflection. Each cycle closed by daily exam. The data collected by observation and examination at daily based. The data analised by narative descriptive analysis and statistical descriptive analysis. The implementation succes if the improvement of the learning process and the number of students reach KKM increase at daily examination I and daily examination II. The research result from the observation form shows that teacher and student activity are better after the treatment implemented. More than half students actively participated in the learning process, as discuss, presented LKS, responded to presenter group, and gave the learning conclusion. The students also tried to solve the quiz from teacher in a great manner. The number of students whose achieved basic score of KKM,; daily examination I (first cycle), and daily examination II (second cycle) are 21.74%, 39.13% and 60.87%. This research shows that cooperative learning of Talking Stick can improve learning process and increase mathematic learning evaluation for VIIID of SMP Islam Terpadu Bangkinang.